Oceans'10 Ieee Sydney 2010
DOI: 10.1109/oceanssyd.2010.5603611
|View full text |Cite
|
Sign up to set email alerts
|

Case study of phytoplankton blooms in serangoon harbor of Singapore

Abstract: A recent algal bloom in the East Johor Strait has led to the damage of marine life in the water channel. This has lead to heavy economic losses to the fish farms located along the water channel. There is a desire to study and be able to predict the occurrences of algal blooms so that their effects on the fish industry can be reduced. Many factors such as weather patterns, tidal conditions and nutrient content in the water contribute to the extent of the eutrophication. This paper describes the design of experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…As the increase in N compared to P or Si also results in an increase in microbial biomass, we suggest that nitrogen is the limiting nutrient in preventing the over-proliferation of photosynthetic microorganisms. This has also been mentioned in past studies 10, 12 .…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…As the increase in N compared to P or Si also results in an increase in microbial biomass, we suggest that nitrogen is the limiting nutrient in preventing the over-proliferation of photosynthetic microorganisms. This has also been mentioned in past studies 10, 12 .…”
Section: Discussionsupporting
confidence: 84%
“…As mentioned in the sections above, water mixing in the Johor Strait is primarily driven by tides (Figure S4). Previous studies have also concluded that blooms happen more frequently during neap tides when tidal mixing is at its minimum, due to the higher cell densities during a stable water column 10,12 . However, we propose that stratification during minimum tidal mixing may also prevent the predators (grazers, viruses) from reaching their target preys.…”
Section: Harmful Algal Blooms May Be Controlled From Both the Top-dow...mentioning
confidence: 99%
See 2 more Smart Citations
“…The co-occurrence would also imply the mixing condition of open and coastal water in the estuary . O'boyle and Silke (2010) and Ooi et al (2010) showed the role of tides in controlling the algal abundance in Singapore water. The condition might be important to maintain the composition of plankton species in the Sungai Pulai estuary.…”
Section: Discussionmentioning
confidence: 99%